The roles of inflammasomes in cancer - Zihan Deng; Lisen Lu; Binghui Li; Xiujuan Shi; Honglin Jin; Weidong Hu (Frontiers in Immunology, 2023)
Inflammation is a key characteristic of all stages of tumor development, including tumor initiation, progression, malignant transformation, invasion, and metastasis. Inflammasomes are an important component of the inflammatory response and an indispensable part of the innate immune system. Inflammasomes regulate the nature of infiltrating immune cells by signaling the secretion of different cytokines and chemokines, thus regulating the anti-tumor immunity of the body. Inflammasome expression patterns vary across different tumor types and stages, playing different roles during tumor progression. The complex diversity of the inflammasomes is determined by both internal and external factors relating to tumor establishment and progression. Therefore, elucidating the specific effects of different inflammasomes in anti-tumor immunity is critical for promoting the discovery of inflammasome-targeting drugs. This review focuses on the structure, activation pathway, and identification methods of the NLRP3, NLRC4, NLRP1 and AIM2 inflammasomes. Herein, we also explore the role of inflammasomes in different cancers and their complex regulatory mechanisms, and discuss current and future directions for targeting inflammasomes in cancer therapy. A detailed knowledge of inflammasome function and regulation may lead to novel therapies that target the activation of inflammasomes as well as the discovery of new drug targets.